2018
DOI: 10.1016/j.biocontrol.2018.05.007
|View full text |Cite
|
Sign up to set email alerts
|

A simulation-based method to compare the pest suppression potential of predators: A case study with spiders

Abstract: A B S T R A C TAssessing and comparing the pest killing capacity of predators is a crucial but laborious task during the implementation of sustainable farming systems. Critical attributes of assessment include quantifying predator's attack rate (a) and handling time (T h ). The maximum attack rate (T/T h ) (i.e. the maximum number of prey that can be attacked by a predator during the time interval (T) considered) could be a more precise and interpretable indicator of the potential suppression of pests exerted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…overlapped with those obtained byBenhadi-Marín et al (2018).Regarding the multiple-prey experiments, our results clearly demonstrated that the presence of alternative prey can shift the predatory efficiency of a generalist predator on a target prey species. For the single-prey experiments, the most and the least efficient spider species against C. capitata were H. rufipes and S. globosum, respectively.…”
supporting
confidence: 74%
See 1 more Smart Citation
“…overlapped with those obtained byBenhadi-Marín et al (2018).Regarding the multiple-prey experiments, our results clearly demonstrated that the presence of alternative prey can shift the predatory efficiency of a generalist predator on a target prey species. For the single-prey experiments, the most and the least efficient spider species against C. capitata were H. rufipes and S. globosum, respectively.…”
supporting
confidence: 74%
“…Finally, the maximum attack rate T/T h (i.e., the maximum number of prey that can be attacked by a predator during the time interval considered) was estimated for each spider species as 24/T h and its confidence intervals generated using the simaR library (Benhadi-Marín et al, 2018). In order to test the effect of additional prey species within the arenas, the multiple-prey functional response analysis was performed for each spider species as described for the single-prey functional responses considering C. capitata as target prey ignoring the other prey species, and then compared with the single-prey functional response assays through the confidence intervals.…”
Section: Functional Response Assaysmentioning
confidence: 99%
“…The confidence limits (95%) were determined to consider the differences between the attack rate (a) and the handling time (h) between the three developmental stages using the frair_boot function from the same package. We calculated the maximum attack rate (T/h) and its 95% confidence limits using the function Max_attackRates from the simaR package [32].…”
Section: Discussionmentioning
confidence: 99%
“…The ratio of 1/T h represents the maximum predation rate considering a predator that spends all its time handling (i.e., 24 h here). The CIs for maximum predation rate were obtained from a set of 20 simulated samples, and 50 datasets (i.e., 50 simulated replicates) were generated for this study by using "simaR" R software package (Benhadi-Marín et al, 2018). Again, significant differences in maximum predation rates among the temperatures were calculated by non-overlapping CIs.…”
Section: Functional Response Assaysmentioning
confidence: 99%